The Effect Analysis of Coating Thickness Variation and Mixture Composition of Magnesium – Flake Glass on Epoxy Coating on Abrasive Resistance, Adhesion Strength, and Prediction of Corrosion Rate of ASTM A36 Steel Plate - Herman Pratikno; Hasan Ikhwani; Yudiardana Tridantoko Susarno (Department of Ocean Engineering, 2020)
Steel cannot be separated from the marine manufacturing industry. It is important to control the corrosion rate of steel used for offshore structures. The coating method can be used in mobilization areas and splash zones that have high corrosion rates due to sustained friction loads in the marine environment. The purpose of this study was to analyze the different in adhesion strength, abrasion resistance, and corrosion rate prediction of ASTM A36 low carbon steel plate with coating thickness variations of 300µm, 500µm, and 700µm and Magnesium Carbonate - Flake Glass mixture variations of 10%, 20%, and 30%. In the pull-off test, the highest value of adhesion strength was obtained from specimen with 300µm coating thickness and 10% Magnesium Carbonate - Flake Glass mixture with a value of 5.67 Mpa. The highest abrasion test value was obtained from specimen with 700µm coating thickness and 30% Magnesium Carbonate - Flake Glass mixture with a value of 0.91 Wear Cyces per Micrometer. Whereas in the three cells electrode test, the highest value was found at specimen with 700µm coating thickness and 30% Magnesium Carbonate - Flake Glass mixture with a value of 0,00010 mmpy.